The Butte Irish: Class and Ethnicity in an American Mining Town, 1875-1925 - Seager, Allen (Labour / Le Travail, 1992)
The article reviews the book, "The Butte Irish: Class and Ethnicity in an American Mining Town, 1875-1925," by David M. Emmons.
Keywords: BOOKS – Reviews; BUTTE Irish: Class & Ethnicity in an American Mining Town 1875-1925; The (Book); EMMONS; David M.; Ethnicity; Nonfiction